Allopachria longyanensis sp. n. from China (Coleoptera: Dytiscidae) - Ji, Lanzhu; Guo, Cheng; Bian, Dongju (Zootaxa, 2014)
Since the revision of the genus Allopachria Zimmermann, 1924 (Wewalka 2000), a total of 13 new species have been added to this genus (Wewalka 2010; Bian & Ji 2010, 2012; Bian et al. 2013). Together with Allopachria longyanensis sp. nov., the genus now includes 47 known species.        The new species was detected among museum material, collected in 1997 in the Fujian Province, China. Specimens were examined under an Olympus SZX16 stereomicroscope, and further details were studied using an Olympus BX51 compound microscope. The studied material is deposited in the Institute of Applied Ecology, Shenyang, Chinese Academy of Sciences.